The Effect Of Liquidity, Profitability And Solvency On Going Concern Audit Opinions - Agia Syafitria Syafril; Ayi Srie Yuniawati; Nining Kurniasih (LPPM Universitas Sebelas April, 2021)
Financial ratios are created with the use of numerical values taken from financial statements plays an important role in detecting the condition of an entity. The result of these financial ratios are used to assess management performance can be used as an evaluation of things that need to be done so that management performance can be improved or maintained in accordance with company targets. This purpose of this research is to find the effect of liquidity, profitability and solvability on going concern audit opinion either simultaneously or partially. The method used in this research is logistic regression and analysis tool used in this research was Statistical Package for the Social Sciences 25 (SPSS 25) with a significance level of 0,05. Based on the partially test indicate that liquidity does not have an effect on going concern audit opinion with a significance level of 0,212, profitability does not have an effect on going concern audit opinion with a significance level of 0,466 and solvability does not have an effect on going concern audit opinion with a significance level of 0,410. While simultaneously have an effect on going concern audit opinion with a significance level of 0,000. The management of the retail trade company must strive to continue to increasing profits each year and offset by decrease of company’s liabilities. And improve good performance by increasing the effectiveness of management in managing their resources.